Exosomal circular RNAs: Biogenesis, effect, and application in cardiovascular diseases - Hu, Xiaoyi; Qin, Hongran; Yan, Yi; Wu, Wenhui; Gong, Sugang; Wang, Lan; Jiang, Rong; Zhao, Qinhua; Sun, Yuanyuan; Wang, Qian; Wang, Shang; Zhao, Hui; et al. (Frontiers in Cell and Developmental Biology, 2022)
As natural nanoparticles, exosomes regulate a wide range of biological processes via modulation of its components, including circular RNAs (circRNAs). CircRNAs are a novel class of closed-loop single-stranded RNAs with a wide distribution, and play diverse biological roles. Due to its stability in exosomes, exosomal circRNAs serve as biomarkers, pathogenic regulators and exert therapeutic potentials in some cardiovascular diseases, including atherosclerosis, acute coronary syndrome, ischemia/reperfusion injury, heart failure, and peripheral artery disease. In this review, we detailed the current knowledge on the biogenesis and functions of exosomes, circRNAs, and exosomal circRNAs, as well as their involvement in these cardiovascular diseases, providing novel insights into the diagnosis and treatment of these diseases.